The Effect of Nursing Students' Self-Efficacy on Patient-Centered Communication During the COVID-19 Pandemic: The Mediating Effect of Learning Burnout - Wang, Jing; Zheng, Qiuyue; Song, Wei; Wei, Ling (Frontiers in Psychiatry, 2021)
Background: The outbreak of the 2019 coronavirus disease (COVID-19) has put the global health system under the spotlight. As part of the medical workforce, nurses play an important role in interacting with and caring for patients, hence patient-centered communication (PCC) has been emphasized in nursing education. Thus, it is worth investigating how future nurses perceive PCC and the factors that affect it under the special circumstances of COVID-19. For this purpose, the present study analyzed the mechanisms underlying the association between self-efficacy and nurse–patient communication tendency through learning burnout among nursing students during the COVID-19 pandemic. Methods: The general self-efficacy questionnaire, college students’ learning burnout scale, and doctor–patient communication tendency scale were used to survey 2231 nursing students in higher vocational medical colleges at the start of COVID-19 pandemic. Results: General self-efficacy can directly negatively affect the degree of nursing students’ overall nurse–patient communication, including caring, sharing and health promotion. Dejection from learning burnout partially mediated the relationships between self-efficacy and caring, and between self-efficacy and sharing, but fully mediated the relationship between self-efficacy and health promotion. Reduced personal accomplishment partially mediated between self-efficacy and caring, while it fully mediated between self-efficacy and health promotion, but did not play a role in the sharing model. Conclusion: Self-efficacy affects nurse–patient communication through learning burnout. Specifically, dejection and reduced personal accomplishment—two of the aspects of learning burnout—may compromise nursing students’ willingness to engage in PCC. Thus, the importance and meaningfulness of PCC, especially during critical health situations such as pandemics, should be emphasized further in future nursing education.